Epistemologias outras: processos educativos entre quilombismos e capoeiras - Oliveira, Gilmar Araujo de (2023)
This doctoral research was developed in collaboration with Kilombo Tenondé (located in the village of Bonfim, city of Valença, in the interior of the state of Bahia), which is based on the principles of the encounter between culture and nature, as well as the preservation of ancestral heritage. In African and indigenous cultures, this heritage is related to the connection with Nature as a sacred place; collective relationships marked by solidarity, plurality, and integration; the valorization of the body as a sacred and cultural space; and the holistic notion of human development, where body and mind, spirit and natural environment are integrated. The investigation is based on the struggles of quilombos (communities formed by descendants of escaped African slaves) since their genesis, the difficulties encountered in land demarcation, and the quilombista perspective of Kilombo Tenondé, which presents itself as a possibility of confronting the coloniality of being, knowing, and power. It allows us to think about the mechanisms that promote the invisibility of other forms of knowledge and the lives of human beings and territories that have been victims of modernity/coloniality. Through the testimonials of frequent visitors to Kilombo Tenondé, the main objective is to identify, describe, and understand the emerging educational processes within this space. Data analysis is being conducted through Generative Themes, which are considered a proposal that aims to be consistent with a new way of conceiving knowledge and human development, emerging from the epistemology present in the practice of Capoeira. These themes are: Gingar (swaying), Esquivar (dodging), Combater (fighting), and Transcender (transcending). Today, the continuity of quilombos and the spaces built within this perspective represent the possibility of transcending modernity. It is a confrontation with the coloniality of being, knowing, and power, a process that allows the breaking of a cycle that racialized and subjugated, and enables us to think about the mechanisms that promote the invisibility of Other forms of knowledge and the lives of human beings and territories that have been victims of modernity/coloniality. Finally, we consider quilombos as possibilities for thinking about a pluriversal education that seeks inclusion and equity, fighting against historical erasure.